2009
DOI: 10.1587/transinf.e92.d.1225
|View full text |Cite
|
Sign up to set email alerts
|

A Solution of the All-Pairs Shortest Paths Problem on the Cell Broadband Engine Processor

Abstract: SUMMARYThe All-Pairs Shortest Paths (APSP) problem is a graph problem which can be solved by a three-nested loop program. The Cell Broadband Engine (Cell/B.E.) is a heterogeneous multi-core processor that offers the high single precision floating-point performance. In this paper, a solution of the APSP problem on the Cell/B.E. is presented. To maximize the performance of the Cell/B.E., a blocked algorithm for the APSP problem is used. The blocked algorithm enables reuse of data in registers and utilizes the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The importance of efficient processing of the APSP problem has led to a substantial amount of previous work that deals with the design and optimisation of APSP either for commodity processors [6,7,8], or for dedicated hardware [9,10,11,12]. Matsumoto et al [6] proposed a CPU-GPU hybrid system that is reported to have outperformed previous work on APSP for commodity processors.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of efficient processing of the APSP problem has led to a substantial amount of previous work that deals with the design and optimisation of APSP either for commodity processors [6,7,8], or for dedicated hardware [9,10,11,12]. Matsumoto et al [6] proposed a CPU-GPU hybrid system that is reported to have outperformed previous work on APSP for commodity processors.…”
Section: Related Workmentioning
confidence: 99%
“…Because of the small-world phenomenon the number of vertices in each BFS level grows very rapidly, leading to most edges being examined in one or two BFS levels, the critical BFS levels. Algorithm 4 describes the bottom-up algorithm that replaces lines (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) in Algorithm 3, i.e. steps 1-4.…”
Section: Hybrid Bfs Kernelmentioning
confidence: 99%
“…On the other hand, in [12], they focus on solving the shortest paths problems for all pairs of nodes, where the advantages of using the CBE are demonstrated. As such, this research focuses on computing the Kleene star of the weighted adjacency matrix of a DAG type, and an implementation of this using SIMD instructions [13] and multiple cores in parallel [14], both of which are available on the CBE, is carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Some attempts to implement the transitive closure on the CELL can be found in the literature. Among them, we point out the works described in [5] (up to 50 GFLOPS) and in [8] (up to 78 GFLOPS in perspective). The two solutions are both based on a block partitioning of the basic Warshall-Floyd procedure together with ad-hoc memory optimization and efficient global synchronization.…”
Section: Introductionmentioning
confidence: 99%